Procesy zmian we wzajemnych stosunkach finansowych państw socjalistycznych - Olszewski, Andrzej (Wydział Prawa i Administracji UAM, 1983)
The article presents a development of financial relations of the socialist states in the years of 1945—1963 and 1964—1982. Conditioning of the first period, forming and developing bilateral financial relations, is presented in the aspect of strong trends of protection of newly constructed industry, limited supply of export goods and inelastic demand on certain products. Circumstances of the second period which gave rise to technical and settling conditions for multilateral settlements are discussed in the latter part, they were not able to relieve a trade system of the socialist countries from the bilateral balancing. Discussing a complex problem of efficiency of multilateral settlements, the author quotes opinions of international finances' specialists and researchers and seeks for new substantial and technical solutions in order to arrive to an agreement between principles of state controlled economy and demands of international trade in the aspect of settlements. In the author's opinion, models of cash settlements between the socialist countries are unsatisfactory at their present stage. The author advocates that requirements of life have to be followed: the conditions of foreign trade are varying, world's economy is not static, supply of goods and services and demand are constantly fluctuating as well as world prices. It is therefore necessary to introduce a reasonable multilaterality of settlements making for stimulation of currency and increase of weight of finances in international settlements and in consequence- for multilateral balancing of trade turnover. In view of the tendencies to isolate socialist countries in the foreign trade, the author emphasises the need to concentrate efforts to create better currency system which would, under the influence of developing CMEA cooperation, improve multilateral settlements. Although payments turnover is functioning efficiently in the CMEA countries by means of the transfer ruble, the article indicates that major problems in the trade between socialist countries are caused by the fact that each socialist state, in order to balance its foreign trade according to plan, establishes quotas, attempts at bilateral balancing of a foreign trade and links directly a volume of exports and imports of deliveries under contract. Bilaterality understood in that way diminishes utility of transfer ruble and its flexibility in settlements and results in ruble's failure to perform its functions in the international trade. In the following remarks the author discusses the role of transfer ruble in settlements in socialist states as a product of the currency system of these states and of the principle of inconvertibility of national currencies, he is also trying to determine whether transfer ruble is a contractual unit of settlement predominated by elements of bilateralism or it is a type of international currency. The author adopts a notion of transfer ruble as an international currency, in its narrow meaning, i.e. which is recognized solely by those states which had created it, as their common unit of account. The article attributes functions of money sui generis to transfer ruble: a scope in which the ruble can perform classical functions of money is described, as a standard of value, as a tender, as a means of accumulation of value. Various views of scientists and financial experts are quoted in this respect. In conclusion, the author admits that transfer ruble is not an international currency in the wide meaning of this word and should be classed among extramonetary units of settlement. Present forms of trade between socialist countries should be, in the authors opinion, altered to overcome a "product for product" barrier, to extend the trade turnover and to create a possibility of converting a value expressed in one currency into another currency. This requires the existence of real exchange rates and a national currency should act as a tender not only in the country but also abroad. Estimating real financial relations of trade and settlements, the author speaks for improving the existing collective currency and elaborating a program in future aiming at introducing convertible currency of the CMEA states or, at least, a currency of partially limited convertibility.
Processes of change in mutual financial relations of the socialist states